Penerapan Media Multiplatfrom dalam Pembelajaran IPS Abad 21 - Salsabila Deti; Salshabila Febrianti Sukmana; Yona Wahyuningsih (Jurnal Ilmiah Wahana Pendidikan, 2023)
Learning is currently taking place continuously, from time to time until now. In the digital era of the 21st century, it brings many impacts that should not be underestimated in the world of education, especially education in Indonesia. In this century, teachers and students are required to be technology literate where technology is currently developing rapidly. Digital learning is a very sophisticated medium that is highly renewable. The benefits that can be obtained from this digital media, especially in the scope of education, include increasing the involvement of a student in learning activities, helping students in applying complex concepts and making students who have critical awareness. In today's digital era, it is imperative to innovate in learning at every educational institution. Utilization of digital learning as a learning tool which certainly has a good effect on the emergence of learning motivation in students, so that in digital learning it is expected that student learning achievements can be achieved optimally.